2012
DOI: 10.1103/physrevlett.108.107206
|View full text |Cite
|
Sign up to set email alerts
|

Magnetization Reversal of Individual Co Nanoislands

Abstract: We investigate the magnetization reversal of individual Co islands on Cu(111) in the size range of N=700 to 18,000 atoms by spin-polarized scanning tunneling microscopy at 8 K. The switching field H(sw) changes with island size in a nonmonotonic manner: it increases with island size and reaches a maximum value of 2.4 T at N=5500 atoms, and it decreases for larger islands. We extract the energy barrier for magnetization reversal as a function of island size. The maximum H(sw) corresponds to an energy barrier of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
69
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(74 citation statements)
references
References 22 publications
4
69
1
Order By: Relevance
“…The existence of a magnetic field threshold for reversal of a magnetic island in the presence of anisotropy has been studied experimentally in detail in Ref. 10; it was analyzed in a classical context 10 with a field threshold equal to 2K μ in the T = 0 K limit (μ is the magnetic moment per atom equal to gμ B S with the present notations). K is the anisotropy energy per atom, i.e., the energy barrier to reversal for a single atom, equal to equal to the quantum threshold given by Eq.…”
Section: A Effect Of the Longitudinal Anisotropy ( D = 0 E = 0)mentioning
confidence: 99%
See 2 more Smart Citations
“…The existence of a magnetic field threshold for reversal of a magnetic island in the presence of anisotropy has been studied experimentally in detail in Ref. 10; it was analyzed in a classical context 10 with a field threshold equal to 2K μ in the T = 0 K limit (μ is the magnetic moment per atom equal to gμ B S with the present notations). K is the anisotropy energy per atom, i.e., the energy barrier to reversal for a single atom, equal to equal to the quantum threshold given by Eq.…”
Section: A Effect Of the Longitudinal Anisotropy ( D = 0 E = 0)mentioning
confidence: 99%
“…At the time of the injection of the tunneling electron, a sharp change of the population of all the states in the manifold is visible, corresponding to the inelastic effect of the tunneling electrons [Eq. (10)]; most of these changes are sharp drops due to the excitation toward spin waves. For example, the sharp drop at t = 0.5 ns in the population of the M Tot = 5 state in the S Tot = 5 manifold (full green line) is due to excitation of higher-lying spin waves.…”
Section: Magnetization Switch Induced By Injected Electronsmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 1(a) shows a schematic illustration of the preparation of a ferromagnetic tip on the surface of Fe 1+y Te: by collecting excess Fe (Fe-II) atoms from the surface of the material, which are attached to the apex of the STM tip, the tip is rendered magnetic. Experiments on cobalt islands on Cu(111) show that in order to obtain a magnetic cluster which is stable at temperatures below 10K on the order of 100 atoms will be required [10]. Fig.…”
mentioning
confidence: 99%
“…Cobalt bilayer islands on Au(111) are believed to reverse their magnetization by CR up to a size of 600 atoms, while a noncollinear magnon assisted process has been proposed for larger islands [7]. Finally, it was suggested that triangular Co bilayer islands on Cu(111) reverse by a single-element exchange spring mechanism for island sizes up to 7500 atoms, from where reversal takes place by DWs [11]. From these examples it is evident that the reversal kinetics of nanomagnets is complex and that the critical size for the reversal mechanism crossover of each transition metal element strongly depends on the substrate.…”
Section: Introductionmentioning
confidence: 99%